2017
DOI: 10.1515/hukin-2017-0065
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Perceived Coaching Behaviours, Motivation and Self-Efficacy in Wrestlers

Abstract: The current study aimed to determine the relationship between perceived coaching behaviours, motivation, self-efficacy and general self-efficacy of wrestlers who competed in the Super National Wrestling League. The sample consisted of 289 wrestlers. The Self-Efficacy Scale was used to measure self-efficacy perception, the Sports Motivation Scale to measure the motivation of the athletes, the Leadership Scale for Sport to determine perceived leadership behaviours, and the General Self-Efficacy Scale to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
(51 reference statements)
0
12
0
1
Order By: Relevance
“…Leadership scores of those who started sports at the age of 6 and 8 were found to be significantly higher than those who started sports at other ages. Contrary to the studies supporting these findings [49], it is also reported that the age of starting sports does not affect the leadership level [50]. It is stated that with the beginning of school at the age of 6;…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 68%
“…Leadership scores of those who started sports at the age of 6 and 8 were found to be significantly higher than those who started sports at other ages. Contrary to the studies supporting these findings [49], it is also reported that the age of starting sports does not affect the leadership level [50]. It is stated that with the beginning of school at the age of 6;…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 68%
“…More recent studies have also sought to broaden the theory to many other positive emotions, such as pleasantness, calmness, confidence, and motivation, and negative emotions such as apprehension, discouragement, insecurity, and fear, and have been able to attest to the effectiveness of the model. [23][24][25] In addition, research on self-efficacy in the sports field 8,19,26 has elucidated the large cause and effect relationship between self-efficacy and sports performance. Moritz et al 27 conducted a meta-analysis to investigate the relationship between self-efficacy and sports performance.…”
Section: Discussionmentioning
confidence: 99%
“…Through an interactive approach, self-efficacy, considered a personal factor, and environmental determinants interact to produce changes in the athlete's future behavior in a reciprocal way. 2,8 In this context, an important component that interferes in self-efficacy is the level of anxiety. Although the anxiety-performance relationship has been extensively studied in recent decades, there are still no definitive conclusions among researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The GSES (Schwarzer and Jerusalem, 1995) is an established measure of generalized self-efficacy that has been adopted in numerous studies in sport (e.g., Hewett et al, 2017;Sarı and Bayazıt, 2017). The GSES consists of 10 items (e.g., "It is easy for me to stick to my aims and accomplish my goals, " "I can solve most problems if I invest the necessary effort") on a 4-point Likert scale, Cronbach's alphas ranged from 0.76 to 0.90 (Schwarzer and Jerusalem, 1995).…”
Section: General Self-efficacy Scalementioning
confidence: 99%